Step-by-step explanation:
The slope of the line passing through two points is given by,
![\frac{y2 - y1}{x2 - x1}](https://tex.z-dn.net/?f=%20%5Cfrac%7By2%20-%20y1%7D%7Bx2%20-%20x1%7D%20)
13)
![\frac{(0 - y)}{(0 - 2)} = (\frac{ - 3}{2} )](https://tex.z-dn.net/?f=%20%5Cfrac%7B%280%20-%20y%29%7D%7B%280%20-%202%29%7D%20%20%3D%20%20%28%5Cfrac%7B%20-%203%7D%7B2%7D%20%29)
![\frac{ - y}{ - 2} = \frac{ - 3}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20-%20y%7D%7B%20-%202%7D%20%20%3D%20%20%5Cfrac%7B%20-%203%7D%7B2%7D%20)
![y = - 3](https://tex.z-dn.net/?f=y%20%3D%20%20-%203)
option D
14)
![\frac{ ( - 3 - y)}{(1 + 5)} = \frac{ - 1}{6}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20%28%20-%203%20-%20y%29%7D%7B%281%20%2B%205%29%7D%20%20%3D%20%20%5Cfrac%7B%20-%201%7D%7B6%7D%20)
![\frac{ - 3 - y}{6} = \frac{ - 1}{6}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20-%203%20-%20y%7D%7B6%7D%20%20%3D%20%20%5Cfrac%7B%20-%201%7D%7B6%7D%20)
![- 3 - y = - 1](https://tex.z-dn.net/?f=%20-%203%20-%20y%20%3D%20%20-%201)
![- y = - 1 + 3 = 2](https://tex.z-dn.net/?f=%20-%20y%20%3D%20%20-%201%20%2B%203%20%3D%202)
![y = - 2](https://tex.z-dn.net/?f=y%20%3D%20%20-%202)
option C
15)
![\frac{(y - 4)}{( - 5 + 1)} = \frac{1}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%28y%20-%204%29%7D%7B%28%20-%205%20%2B%201%29%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7B4%7D%20)
![\frac{y - 4}{ - 4} = \frac{1}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7By%20-%204%7D%7B%20-%204%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7B4%7D%20)
![- y + 4 = 1](https://tex.z-dn.net/?f=%20-%20y%20%2B%204%20%3D%201)
![- y = 1 - 4 = - 3](https://tex.z-dn.net/?f=%20-%20y%20%3D%201%20-%204%20%3D%20%20-%203)
![y = 3](https://tex.z-dn.net/?f=y%20%3D%203)
option B
16)
![\frac{(y + 3)}{( - 4 - 3)} = \frac{ - 3}{7}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%28y%20%2B%203%29%7D%7B%28%20-%204%20-%203%29%7D%20%20%3D%20%20%5Cfrac%7B%20-%203%7D%7B7%7D%20)
![- (y + 3) = - 3](https://tex.z-dn.net/?f=%20-%20%28y%20%2B%203%29%20%3D%20%20-%203)
![y = 3 - 3 = 0](https://tex.z-dn.net/?f=y%20%3D%203%20-%203%20%3D%200)
option C
Answer:
No, Matt did not solve the equation correctly
Correct Answer: x = 8
Step-by-step explanation:
4(x + 2) = 30
Step 1: Distribute
4x + 2 = 30
This is his mistake, he should completely distribute 4
to x and 2
Step 2: Subtract 2 from both sides/Isolate x
4x = 28
This part is done correctly, but wrong because of Step 1
Step 3: Divide both sides by 4
x = 7
This is correct, but again, he messed up on Step 1
<h3>
Let's find the correct answer to this equation:</h3><h3>4(x +2) = 30</h3>
Step 1: Distribute
Remember to distribute 4 to all terms in the parenthesis.
4(x + 2) = 4(x) + 4(2)
= 4x + 8
4x + 8 = 30
Step 2: Subtract 8 from both sides/Isolate x
Move all the terms that do not belong to x to the other side. We can do this by subtracting 8 from both sides
(opposite operation of adding 8)
4x + 8 = 30
4x = 30 - 8
4x = 32
Step 3: Divide both sides by 4/Isolate x
Now we want x by itself. Since x is being multiplied by 4, we have to use the opposite operation, dividing by 4, to have x on one side by itself
4x = 32
4(x) = 32
x = 32 ÷ 4
x = 8
-Chetan K
Answer: 5 minutes
Step-by-step explanation:
Answer:they would pay a total amount of $9
Step-by-step explanation:
Scott and Tom rent a boat at Stow Lake. They start at 10:15 and end at 11:45. The number of hours for which they rented the boat would be
11:45 - 10:15 = 1 hour 30 minutes = 1.5 hours.
Converting to minutes, It becomes
60 + 30 = 90 minutes.
The boat rental costs $1.50 for every 15 minutes. Therefore, the total amount of money that they would pay is
90/15 × 1.5 = $9
Answer:
Step-by-step explanation:
First you have to add up everything and get the answer which is 24. Then you have to consider that there are 6 yellow jelly beans. So you would have to put it as a fraction. Which would be... 6/24 hope I helped